Neomodernistas de 1945: uma querela de gerações - Velloso, Ana Paula Meyer (2017)
The present work refers to the so-called Generation of 45 in Brazil, also known as neomodernist, whose main characteristic was the rupture of the modernist pattern imposed by previous generations. The authors of the generation of 45 presented extensive innovations in aesthetic research, also in the forms of expression within Brazilian literature, and it was a literary movement that reviewed and criticized modernism, but did not constitute an organic group assembled through a manifesto. The main objective of this research centered on the generational question of these Brazilian writers, focuses on the sociology of culture, and demonstrates how their trajectories intertwine and influence the exchange of ideas, with big changes in literary production, in explicit opposition to the movements of the 1920s. It is proved that there was, after the modernists of 22, a new generation of critics, poets and essayists, known as the generation of 45. The result of the survey concerning the trajectories of the participants of different groups at that time, shows exclusively that these groups can be seen, therefore, as a unique generation, that sought recognition in the literary field of that period. The idea of a single generation was invoked at the very time it occurred, both by the new characters and by the observers of the time. The way how the 1945 generation was organized, was explained with Mannheim concepts, and proved extensively through the research of the personal trajectories of the members of that generation. The differences between this generation and the previous one, another important point of discussion at the time, were also analyzed in the case studies of the research, showing how the concrete groups of the 1945 generation manifested themselves in opposition to the 1922 modernists, through articles and Poems they published in literary magazines and newspapers, often in supplements and literary foot notes, characteristic of this generation. Other literary manifestations also occurred, through poetry conferences, clubs and literary cafes, an important legacy of that time. Thus, the present work identifies and registers the role and importance of these publications in the origin and development of Brazilian cultural production of that period, since it was in this context that the new writers of the time carried out their works. Magazines and newspapers were voices for authors who pronounced themselves on their pages with articles, manifestos, critical essays, poems, short stories, fragments of novels, literary reviews, etc. The generation of 1945 is also a custodian of greater state intervention in education in the 1930s, in one hand, at the federal level, by the initiatives of the Ministry of Education and Public Health, in the other, with the founding of the University of São Paulo, by the state government of São Paulo. This phenomenon presents itself as an important counterpoint to the previous generation, also called the generation of “self-taught polygraphs”. Finally, the conclusion is that the Generation of 45 is in fact a generation, a cohesive movement, with historical relevance, specially by it’s independent, autonomous and divergent positioning in relation to previous generations